Criteria selection method in design evaluation for product development using integrated Fuzzy-AHP - Turan, Faiz Mohd
Design concept evaluation plays a critical role in the early phases of product development as it has significant impact on the downstream development processes as well as on the success of the product developed. In this paper, a novel methodology has been developed involving three stages. The preliminary stage is screening all the criteria from different viewpoints using TRIZ. The second stage uses Fuzzy-AHP to obtain the alternatives weight, and the final stage verifies the rank of alternatives by a Rough-Grey Analysis. This method will give the designers more effective, objective and relevant information in order to make the final decision. A case example from industry is presented to demonstrate efficacy of the proposed methodology. The result of the example shows that the integration of TRIZ, Fuzzy-AHP and Rough-Grey Analysis provided a novel alternative of existing methods to perform design concept evaluation.